A CRITICAL APPROACH OF GUS BAHA TO SHEIKH SITI JENAR’S THOUGHT IN THE NUSANTARA TAFSIR METHODOLOGY - Siswoyo Aris Munandar; M. Fahrurrozi (Sekolah Tinggi Agama Islam Sadra, 2025)
Sheikh Siti Jenar’s thoughts on Manunggaling Kawula Gusti often cause controversy in the Nusantara Islamic tradition, especially related to the concept of wahdatul wujud, which is considered to equate humans with God. KH Ahmad Bahauddin Nursalim (Gus Baha), as one of the contemporary scholars of Nusantara, provides criticism of this thought through a unique interpretive approach in the Nusantara interpretation methodology. This study uses a qualitative approach with literature studies and text analysis of Gus Baha’s works and relevant sources on Nusantara interpretation and Sufism. The ijmālī and contextual interpretation approaches applied by Gus Baha are also analyzed to understand his criticism of Sheikh Siti Jenar. This paper aims to describe and analyze Gus Baha’s critical approach to Sheikh Siti Jenar’s thoughts in Nusantara interpretation. The research results show that Gus Baha rejects claims that contradict sharia, particularly the teachings of Manunggaling Kawula Gusti, emphasizing the importance of balancing sharia and the essence of Islam Nusantara. Gus Baha’s approach, which prioritizes contextualization and accessible language, makes his interpretations relevant to the people of the archipelago.